What do we know about business angels' decision making research development? - Vasić, Dina (Economic and business review, 2022)
Business angels (BAs) mitigate the financial gap of early-stage ventures and get actively involved in ventures they invest in. Their crucial role in the start-up ecosystem is spurring interest in their decision-making processes when making investments. However, the research about their investment decision making is crumpled. So far, we know the knowledge base about BA decision making comes from a blend of interdisciplinary studies where psychology and finance had a significant impact in pushing the research to new levels. With this study, we review knowledge dyads in the BA decision-making field through bibliometric co-citation analysis.
Keywords: business angels; enterprises; innovations; inovacije; podjetje; poslovni angeli